Mesenchymal stem cells promote lymphangiogenic properties of lymphatic endothelial cells - Robering, Jan Willem; Weigand, Annika; Pfuhlmann, Romy; Horch, Raymund E.; Beier, Justus; Boos, Anja (Journal of Cellular and Molecular Medicine, 2018)
Lymphatic metastasis is one of the main prognostic factors concerning long-term survival of cancer patients. In this regard, the molecular mechanisms of lymphangiogenesis are still rarely explored. Also, the interactions between stem cells and lymphatic endothelial cells (LEC) in humans have not been well examined. Therefore, the main objective of this study was to assess the interactions between mesenchymal stem cells (MSC) and LEC using in vitro angiogenesis assays. Juvenile LEC were stimulated with VEGF-C, bFGF, MSC-conditioned medium (MSC-CM) or by co-culture with MSC. LEC proliferation was assessed using a MTT assay. Migration of the cells was determined with a wound healing assay and a transmigration assay. To measure the formation of lymphatic sprouts, LEC spheroids were embedded in collagen or fibrin gels. The LEC's capacity to form capillary-like structures was assessed by a tube formation assay on Matrigel® . The proliferation, migration and tube formation of LEC could be significantly enhanced by MSC-CM and by co-culture with MSC. The effect of stimulation with MSC-CM was stronger compared to stimulation with the growth factors VEGF-C and bFGF in proliferation and transmigration assays. Sprouting was stimulated by VEGF-C, bFGF and by MSC-CM. With this study, we demonstrate the potent stimulating effect of the MSC secretome on proliferation, migration and tube formation of LEC. This indicates an important role of MSC in lymphangiogenesis in pathological as well as physiological processes.
EVALuna2:211472